2013
DOI: 10.1016/j.jtcvs.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Fontan fenestration closure and event-free survival

Abstract: Objectives The purpose of this study was to evaluate the association of open and closed Fontan fenestration status with event-free survival. Methods All patients who underwent a fenestrated Fontan procedure at our institution from January 1994 through June 2007 were reviewed. Patient information was obtained from medical records. Patients were assigned to one of two study groups, Open vs Closed, based on their most recent fenestration status. Clinically relevant morbid events were tabulated and Kaplan-Meier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 14 publications
2
18
0
1
Order By: Relevance
“…In the literature, there is a wide variation in the rate of spontaneous closure of the fenestration ranging from 8% to 29%. 16,17 Consistent with this, the rate of spontaneous closure in our patients was 22%.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the literature, there is a wide variation in the rate of spontaneous closure of the fenestration ranging from 8% to 29%. 16,17 Consistent with this, the rate of spontaneous closure in our patients was 22%.…”
Section: Discussionsupporting
confidence: 89%
“…Currently, there is limited data on medium and long term effects and the rate of spontaneous closure of the fenestration. In the literature, there is a wide variation in the rate of spontaneous closure of the fenestration ranging from 8% to 29% . Consistent with this, the rate of spontaneous closure in our patients was 22%.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the extracardiac Fontan, a path may be established by creating a small hole in both the continuation of the inferior vena cava and the atrium, and then surgically connecting them together. We remark that fenestrations may be given at the time of Fontan conversion, usually with the expectation that the small hole or conduit will eventually close [14]. Our modeling focuses on quantifying the effect of fenestrations created after the Fontan surgery in response to complications.…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of studies have shown no significant difference in early or late mortality, duration of pleural drainage, or length of hospital stay between fenestrated and nonfenestrated patients . Fenestration closure has been associated with greater arterial oxygen saturation, reduced need for anticongestive medication, and improved somatic growth but it seems to have a limited effect on event‐free survival or long‐term outcome .…”
Section: Discussionmentioning
confidence: 99%